Student perceptions on the implementation of Learning Management System (LMS) in teaching of English for academic writing course. - Ismail, Zuraidah (2011)
This paper is a report on the findings of student perceptions on the implementation of Learning Management System (LMS) in the teaching of English for Academic Writing (EAW) Course. Data was collected through closeended and open-ended questions, and through lecturer’s observation. The findings suggest that LMS promotes an anytime-anyplace learning environment and assists students in the learning process and assignment completion. The rationale of the study is to enable educators, administrators and policy makers to develop a sound understanding on student perceptions on the use of LMS for EAW Course. Thus further decisions can be carried out to improve elearning for the EAW course and other English courses at the campus.